Making news and making space: Framing Vancouver's Downtown Eastside. (4th December 2012) - Liu, Sikee; Blomley, Nicholas
<x xml:space="preserve">Abstract</x> How is inner city space represented and by whom? Drawing from an extensive framing analysis of print media portrayals of Vancouver's Downtown Eastside between 1996 and 2008, we offer a detailed assessment of the predominately negative portrayal of the neighbourhood, and the centrality of three frames: medicalization, criminalization, and socialization. Certain social actors are given a privileged position in the media in the representation of the inner city. Outsiders are privileged over insiders, with the neighbourhood constituted as a problematic space and its residents as passive victims. The effect is to further the stigmatization of an already marginalized neighbourhood, and to accentuate the disempowerment of its residents.